Elotuzumab for Treatment of Multiple Myeloma (Literature Review) - OM Votyakova (Клиническая онкогематология)
Chemotherapy has been the main treatment option for multiple myeloma for several decades. However, a considerable increase in the life expectancy was observed in multiple myeloma patients when thalidomide, bortezomib and lenalidomide had been introduced into clinical practice. Nevertheless, the disease remains incurable and there is an unmet need in fundamentally new treatment methods. Elotuzumab is a humanized IgG1 monoclonal antibody that specifically targets SLAMF7, an antigen belonging to the signaling lymphocytic activation molecule family, with its high expression detected on myeloma cells. This review presents the mechanism of action of elotuzumab, preclinical data and the main clinical studies of this monoclonal antibody.